The Taming of the shrew - "Shakespeare" (Sweet cherry publishing: China, 2013)
One of Shakespeare s most robust comedies, The Taming of the Shrew, is about Katherine, the ill-tempered daughter of a wealthy merchant in Padua. Katherine is so petulant that her father always believed no man would ever want her as his wife. However, Petruchio, a rich young man, comes into Katherine s life and brings about a great change in her behaviour. This short narrative version of the play has been suitably adapted to help introduce the play to young readers. It can be read by children or read to them by parents who wish to introduce them to the play. It can also be used by teachers as a classroom resource
Keywords: Adaptations Juvenile literature